PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KUALITAS AUDIT, DAN KEPEMILIKAN INSTITUSIONAL PADA AGRESIVITAS PAJAK - Suprimarini, Ni Putu Deiya; Suprasto H, Bambang (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The purpose of this study was to determine the effect of corporate social responsibility, quality audits, and institutional ownership on the tax aggressiveness. The population used is manufacturing companies listed on the Indonesian Stock Exchange 2013-2015 period by using purposive sampling to obtain  about 99 samples data collected with nonparticipant observation. This study used multiple linear regression analysis with the results of the analysis are corporate social responsibility has significant negative effect on the tax agressiveness. Audits quality has significant positive effect on the tax agressiveness. Institutional ownership has no effect on the tax aggressiveness.
Keywords: Tax Agressiveness, CSR, Audits Quality, Institutional Ownership